Application of Value Analysis Techniques on a Rucksack: A Case Study - Utkarsh Tiwari; Omprakash P; V.S. Giri (Budapest International Research and Critics University, 2020)
Manufacturers are allocating more of their resources to achieve customer delight by providing a better quality product and additional features at the lowest possible cost not only to acquire the market for existing product but also to increase and secure the demand for future products.With the increase in trend of travelling, the manufacturers need to meet and exceed the demands of their customers, the most vital demand of travellers are comfortable, reliable and multifunctional backpacks. Therefore, it become a necessity for manufacturers to control the cost and introduce new features to the rucksack.The aim of the paper “Application of Value Analysis Techniques on a Rucksack” is to perform a case study to improve and introduce new features in a rucksack through VA/VE methodology. The essence of value engineering technique involves the critical analysis of the functions of a product over all of its stages and producing a creative and innovative way to achieve the function at the lowest cost. Value analysis is an approach to improve the value of an item or process by understanding its constituent components and their associated costs. It then seeks to find improvements to the components by either reducing their cost or increasing the value of the functions. Upon application of VA methodology, a potential saving and multifunctionality is observed in the rucksack.